Bioaugmentation strategies to enhance long chain fatty acids (LCFA) conversion to methane - Silva, Sérgio (2011)
Bioaugmentation of bioreactors with LCFA-degrading bacteria is a possibility for improving methane production from lipid-rich wastes/wastewaters. Cavaleiro et al. [1] has shown that methane production from oleate (unsaturated LCFA) is faster and more efficient in batch tests bioaugmented with Syntrophomonas zehnderi, a bacterium that is able to degrade a wide range of both saturated and unsaturated LCFA [2]. In this work, anaerobic sludge bioaugmentation with S. zehnderi was studied in order to evaluate: (I) the recovery of bioreactors after an episode of LCFA overload; (II) the potential for decreasing reactor start-up periods. The potential of using S. zehnderi for recovering LCFA-overloaded sludge was tested using anaerobic sludge collected from a oleate-fed bioreactor at three different operation times. Bioaugmentation batches were prepared with LCFA loaded biomasses in the presence of S. zehnderi. Controls were set using inactivated S. zehnderi. Methane yields of 72, 53 and 40% were obtained from the first, second and third collected sludge samples respectively. However, addition of S. zehnderi did not significantly improve LCFA conversion loaded-sludges as similar yields were achieved in non-bioaugmented controls. Fed-batch bioreactor start-up, using a non-acclimated sludge, was attempted in the presence of S. zehnderi. Assays were conducted in the presence and absence of both a solid microcarier (sepiolite) and a substoichiometric amount of ferric hydroxide. Blank (no oleate) and control assays (inactivated S. zehnderi) were also prepared. Bioaugmentation assays with sepiolite and ferric hydroxide showed the highest methane yield, with an observed methane yield 16% higher than in non-bioaugmented controls. The potential of bioaugmenting S. zehnderi as means to recover methanogenic activity of LCFA-loaded biomass was not demonstrated. However faster reactor start-up could be accomplished since higher methane yield was achieved in bioaugmented fed-batch assays in the presence of sepiolite with ferric hydroxide. [1] Cavaleiro, A.J., Sousa, D.Z. and Alves, M.M. 2010. Water Res 44:4940-7. [2] Sousa, D.Z., Smidt, H., Alves, M.M. and Stams, A.J.M. 2007. Int J Syst Evol Microbiol 57:609-15. Acknowledgments: This study has been funded by FEDER, through the COMPETE program, and by Portuguese funds, through Portuguese Foundation for Science and Technology (FCT), in the frame of the project FCOMP-01-0124-FEDER-014784. References: